The Association Of Adiponectin, Homocysteine, B 12 And Folic Acid In Iraqi Women With Preeclampsia And Its Severity - Basima Shamkhi Al Ghazali (مجلة الكوفة الطبية, 2023)
Background: preeclampsia is a common obstetric disorder that remains a leading cause of maternal and perinatal mortality and morbidity. Maternal serum concentrations of adiponectin, folate, homocysteine, and vitamin B12 have been found to be associated with pre-eclampsia. Nevertheless, reported studies involved still not clear with variable reliably. The aim of the present study is to examine the relationship between these biomarkers and pre-eclampsia and its severity in Iraqi population. Aims: The study aims to evaluate the association between maternal serum adiponectin, homocysteine, B12 and Folic acid and preeclampsia and its severity. Study design and setting: A case control study carried out in Al-Zahraa Maternity and Pediatric Teaching Hospital in Najaf city/ Iraq from the 1st of  December 2019 to the 1st of December 2020.